HISTORIA DE LA CLASIFICACIÓN DE LOS ANUROS CON ESPECIAL ÉNFASIS EN LA FAMILIA RANIDAE - Hoyos Hoyos, Julio Mario; Departamento de Biología Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2004)
A review of anuran amphibian classifications covering the period from the late 17th century to the late 20th century is presented here. A special emphasis is given to the classifications of the Ranidae family, taking into account the difficulties that have occurred due to the several points of viewabout the family’s participating taxons. The history of classifications at this level shows that theRanidae family may be a paraphyletic taxon, and that it is actually composed of several differentfamilies.